Implikasi Kategori Ibadah Mahda dan Ibadah Gairu Mahda pada Penetapan Hukum dalam Kitab Taharah Bidāyah al-Mujtahid wa Nihāyah al-Muqtaṣid: Implications of the Categories of Mahda Worship and Gairu Mahda Worship on the Determination of Laws in the Book of Taharah Bidāyah al-Mujtahid wa Nihāyah al-Muqtaṣid - Mahmuddin, Ronny; Ihwan Wahid Minu; Muh. Rafdi (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This study aims to understand and analyze the legal implications between mahda worship and gairu mahda worship in the book of taharah Bidāyah al-Mujtahid wa Nihāyah al-Muqtaṣid. The problems that the researcher raises in this study are: first, how is the construction of the division of worship into mahda and gairu mahda; second, what is the urgency of categorizing worship into mahda and gairu mahda; third, what are the implications of categorizing worship into mahda and gairu mahda on the determination of law in the book of taharah Bidāyah al-Mujtahid wa Nihāyah al-Muqtaṣid. The type of research used in this study is library research. The approach methods used are Islamic law approach, textual approach, and comparative approach. The research findings are: first, worship based on its type is divided into two, mahda worship, namely worship whose 'illah is unknown and gairu mahda worship, namely worship whose 'illah is known. Second, with the categorization of worship as mahda and gairu mahda, a mujtahid is able to distinguish which laws can be likened because its 'illah is known and which cannot be likened because its 'illah is unknown. Third, the categorization of mahda and gairu mahda worship has implications for the book of taharah Bidāyah al-Mujtahid wa Nihāyah al-Muqtaṣid in several issues; ablution and bathing after janabah, washing hands before putting them into a vessel, wiping the head more than once, rukhsah wiping the khuf, and tayammum. The implications of this research include being able to help in determining the correct laws and practices of worship in daily life, especially in the issue of taharah. In addition, by understanding the reasons for the differences among scholars which are rooted in the different categorizations of mahda and gairu mahda worship, Muslims can be more aware in responding to differences of opinion.